A Ycf2-FtsHi Heteromeric AAA-ATPase Complex Is Required for Chloroplast Protein Import. Issue 11 (11th October 2018) - Kikuchi, Shingo; Asakura, Yukari; Imai, Midori; Nakahira, Yoichi; Kotani, Yoshiko; Hashiguchi, Yasuyuki; Nakai, Yumi; Takafuji, Kazuaki; Bédard, Jocelyn; Hirabayashi-Ishioka, Yoshino; Mori, Hitoshi; Shiina, Takashi; et al.
Abstract : A protease-originated membrane-bound AAA-ATPase is involved in preprotein translocation across the inner envelope membrane of chloroplasts as an essential import motor. Abstract: Chloroplasts import thousands of nucleus-encoded preproteins synthesized in the cytosol through the TOC and TIC translocons on the outer and inner envelope membranes, respectively. Preprotein translocation across the inner membrane requires ATP; however, the import motor has remained unclear. Here, we report that a 2-MD heteromeric AAA-ATPase complex associates with the TIC complex and functions as the import motor, directly interacting with various translocating preproteins. This 2-MD complex consists of a protein encoded by the previously enigmatic chloroplast gene ycf2 and five related nuclear-encoded FtsH-like proteins, namely, FtsHi1, FtsHi2, FtsHi4, FtsHi5, and FtsH12. These components are each essential for plant viability and retain the AAA-type ATPase domain, but only FtsH12 contains the zinc binding active site generally conserved among FtsH-type metalloproteases. Furthermore, even the FtsH12 zinc binding site is dispensable for its essential function. Phylogenetic analyses suggest that all AAA-type members of the Ycf2/FtsHi complex including Ycf2 evolved from the chloroplast-encoded membrane-bound AAA-protease FtsH of the ancestral endosymbiont. The Ycf2/FtsHi complex also contains an NAD-malate dehydrogenase, a proposed key enzyme for ATP production in chloroplasts in darkness or in nonphotosynthetic plastids. These findings advance our understanding of this ATP-driven protein translocation system that is unique to the green lineage of photosynthetic eukaryotes.